Optimizing 3D Printing Parameters For Best Mechanical Properties - Kee, Tze Shen (Universiti Sains Malaysia, 2018)
A large number of manufacturing companies are pursuing to additive manufacturing technology, since this technology is absolutely amazing for customized product. As additive manufacturing becomes widely adopted for modeling, prototyping, rapid tooling and short-run applications, the quality control become crucial to be developed in manufacturing business. The intent of this study is to discuss the response quality characteristics control of additive manufacturing technology which subject to critical printing parameters optimization. Fused deposition modelling (FDM) is one of commonly adopted 3D printing system in manufacturing industries. For FDM 3D printing process, layer thickness, infill pattern, extrusion temperature and print speed are the critical printing parameter considered for optimization. Five response to be considered for printing parameters studies, which is ultimate tensile strength, compressive modulus, surface roughness, dimensional accuracy and manufacturing time. Taguchi L9 orthogonal array method is designed for optimization of printing parameters to achieve best quality characteristics of printed parts. Optimum parameters values and effectiveness of printing parameters were analysed using signal to noise ratio (S/N ratio) and analysis of variance (ANOVA). Verification experiment were be conducted to discuss the printing performance of optimum conditions.